THE EFFECT OF AUDIO-VISUAL TEACHING MEDIA ON STUDENTS’ LISTENING COMPREHENSION FOR GRADE EIGHTH AT SMP SWASTA TAMAN ASUHAN PEMATANG SIANTAR - Situmeang, Khaterina Vonbora; Efipanias Manihuruk, Leonita Maria; Ristella Munthe, Melda Veby (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
The aim of this study was to assess the effectiveness of audio-visual teaching media in improving students' listening comprehension. A quantitative approach was utilized, employing a quasi-experimental research design. Pre-tests and post-tests were administered to two whole-class groups: VIII-1 (experimental group, n=22) and VIII-2 (control group, n=22). The sample size consisted of 44 students, determined through purposive sampling. The experimental group received instruction using audio-visual teaching media, specifically movie clips in the listening class, while the control group was taught using audio-recording media. Analysis of the data indicated that the mean score for the pre-test in the experimental group was 42.95, which increased to 70.22 in the post-test. Conversely, the control group had a pre-test mean score of 39.09, which rose to 50.45 in the post-test. By applying the t-test formula, it was discovered that the t-value (5.75) exceeded the t-table (1.68195) with a degree of freedom (df) of 42. Consequently, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Hence, the utilization of audio-visual teaching media had a significant impact on the listening comprehension of eighth-grade students at SMP Swasta Taman Asuhan Pematang Siantar. This study suggests that audio-visual teaching media can be effectively employed as a teaching method to enhance students' listening comprehension skills.